DOI: 10.31274/rtd-180813-10156
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived youth leadership and life skills development among Iowa FFA members

Abstract: The objectives of this study were to: (1) describe Iowa FFA members by their selfperceived youth leadership life skills development, participation in FFA leadership activities, participation in nonFFA leadership activities, achievement expectancy, years in the FFA, age, gender, self-reported grade point average, and place of residence, (2) assess the level of youth leadership life skills development possessed by Iowa FFA members, (3) determine if a relationship exists between self-perceived leadership life ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Ricketts (1983) found that Tennessee vocational agriculture students possess significantly more leadership abilities than nonvocational agriculture student. Domriody and Seevers (1994) Wingenbach, (1995) found that participation in FFA leadership activities, after school jobs, years in FFA, grade point average, and gender were predictors of leadership development.…”
Section: Non-4-h Referenced Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Ricketts (1983) found that Tennessee vocational agriculture students possess significantly more leadership abilities than nonvocational agriculture student. Domriody and Seevers (1994) Wingenbach, (1995) found that participation in FFA leadership activities, after school jobs, years in FFA, grade point average, and gender were predictors of leadership development.…”
Section: Non-4-h Referenced Studiesmentioning
confidence: 99%
“…To accomplish this objective the dependent and independent variables were analyzed using a forced entry multiple regression procedure. This method was chosen because it allows all independent variables to be entered, and remain in, the multiple regression equation (Wingenbach, 1995). Using the forced entry procedure, the independent variables contributing to the explanation of variance in the dependent variable would have a significant t -value.…”
Section: Data Inmentioning
confidence: 99%
See 3 more Smart Citations